Enhanced Hall Effect in Co/Pd Multilayered Nanodomes with Perpendicular Anisotropy - Oyarzun-Medina, S; Michea-Mora, S; Casagrande-Denardin, J (American Institute of Physics, 2017)
In this work, multilayers of Co/Pd with out of plane anisotropy have been deposited on the bottom of porous alumina membranes, forming nanodomes films with 100 and 200 nm diameter. The magnetization reversal of the multilayers is investigated by magnetization curves, extraordinary Hall effect and magnetic force microscopy (MFM) experiments. The results show that as the pore diameter increase, a larger hall resistivity is obtained, compared with the continuous film. © 2017 Author(s).